2020
DOI: 10.1007/s40194-020-00920-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of resolution on the X-ray CT-based measurements of metallic AM lattice structures

Abstract: Additive manufactured (AM) lattice structures have become very prominent in recent times especially in air and spacecraft industry for their lower weight and specific mechanical properties. Their stiffness and strength can be controlled by their geometrical properties, such as the shape and dimensions of the unit cell. Geometrical and dimensional accuracy of the AM lattices is therefore one of the most important requirements to meet the desired functionality as there could be significant deviations in the as-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Moreover, ERT utilizes the intrinsic electromechanical properties of lattice structures and renders effective inspection by propagating current throughout the entire structure. Furthermore, X-ray CT-based measurements or other image processing methods require the structure to be placed between a source and detector while being rotated to obtain multiple projection slices, which requires extensive operational times and computational resources [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ERT utilizes the intrinsic electromechanical properties of lattice structures and renders effective inspection by propagating current throughout the entire structure. Furthermore, X-ray CT-based measurements or other image processing methods require the structure to be placed between a source and detector while being rotated to obtain multiple projection slices, which requires extensive operational times and computational resources [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In order to find out the right set of scanning parameters for the Inconel (3×3×3) lattice structure, the transmission-based approach was utilized which states that a minimal transmission between 10% and 20% is required to reach an optimal signal-to-noise ratio (SNR) [33,34]. The transmission is the ratio between the minimal and the maximal X-ray intensity at the detector, which is expressed in the respective grey values of the X-ray projection.…”
Section: Data Acquisition With X-ray Ctmentioning
confidence: 99%
“…Some of the recent works have studied these limitations e.g. the influence of resolution on measurement results has been studied by Rathore et al [34]. In addition, recent research has reported several solution for beam hardening correction [35] and scattering correction [36,37].…”
Section: Limitations and Outlookmentioning
confidence: 99%